2016
DOI: 10.3835/plantgenome2016.01.0005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Selection for Processing and End‐Use Quality Traits in the CIMMYT Spring Bread Wheat Breeding Program

Abstract: Wheat (Triticum aestivum L.) cultivars must possess suitable enduse quality for release and consumer acceptability. However, breeding for quality traits is often considered a secondary target relative to yield largely because of amount of seed needed and expense. Without testing and selection, many undesirable materials are advanced, expending additional resources. Here, we develop and validate whole-genome prediction models for end-use quality phenotypes in the CIMMYT bread wheat breeding program. Model accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
157
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 42 publications
19
157
8
1
Order By: Relevance
“…Figure S5 shows an example of the predictive accuracy of CORE heading date data in the 2010 Ottawa home‐test population. The accuracies obtained for these independent validations were lower than cross‐validation accuracies, which are in agreement with previous independent validation comparisons (Asoro et al ., ; Battenfield et al ., ) and reflect additional variance in environment and/or genotype‐by‐environment interaction between years, as well as potential differences in population parameters. Differential response to environment is a confounding factor in all types of selection; thus, this reduced accuracy of genomic prediction probably reflects a more realistic metric for the selection of stable and predictable performance in practical breeding schemes.…”
Section: Discussionmentioning
confidence: 99%
“…Figure S5 shows an example of the predictive accuracy of CORE heading date data in the 2010 Ottawa home‐test population. The accuracies obtained for these independent validations were lower than cross‐validation accuracies, which are in agreement with previous independent validation comparisons (Asoro et al ., ; Battenfield et al ., ) and reflect additional variance in environment and/or genotype‐by‐environment interaction between years, as well as potential differences in population parameters. Differential response to environment is a confounding factor in all types of selection; thus, this reduced accuracy of genomic prediction probably reflects a more realistic metric for the selection of stable and predictable performance in practical breeding schemes.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to accurately profile lipids allows for inclusion of these compounds in wheat breeding selection criteria. Many programs are working toward using genomic selection for prediction of end use quality (Battenfield et al 2016). The use of phenotypic data, such as loaf volume, can be problematic as multiple factors influence the trait.…”
Section: Discussionmentioning
confidence: 99%
“…Due to advances in sequencing technology, genome-wide single nucleotide polymorphism (SNP) markers are available through genotyping-by-sequencing (GBS) at a cost conducive to application for genomic selection (Poland and Rife, 2012, Poland et al, 2012). Currently, the cost of genotyping all ~ 10,000 first year yield trials lines is equivalent to phenotyping 2000 lines for processing and end-use quality (Battenfield et al, 2016). Thus, genomic selection, for quality alone will assist in selecting for quality at CIMMYT since all first-year yield trials can be predicted, rather than only the yield trial winners.…”
Section: Genomic Selection For Wheat Quality Improvementmentioning
confidence: 99%
“…Battenfield et al (2016) applied genomic selection to all of the processing and end-use quality traits regularly tested in the CIMMYT spring wheat breeding program as listed above. These traits have variable levels of prediction accuracy, however, they demonstrated that most expensive traits, dough rheology and baking final product, can be predicted with a high degree of confidence.…”
Section: Genomic Selection For Wheat Quality Improvementmentioning
confidence: 99%